2017
DOI: 10.1364/boe.8.002210
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of accuracy in shape sensing of surgical needles using optical frequency domain reflectometry in optical fibers

Abstract: Abstract:We demonstrate a novel approach to enhance the precision of surgical needle shape tracking based on distributed strain sensing using optical frequency domain reflectometry (OFDR). The precision enhancement is provided by using optical fibers with high scattering properties. Shape tracking of surgical tools using strain sensing properties of optical fibers has seen increased attention in recent years. Most of the investigations made in this field use fiber Bragg gratings (FBG), which can be used as dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
49
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 114 publications
(55 citation statements)
references
References 18 publications
0
49
0
2
Order By: Relevance
“…As previously outlined in [22], the MgO-NP fiber induces a beat length of polarization that has a higher frequency than a standard SMF, with polarization switching every few centimeters. This effect is common with the other methods proposed for enhancing the Rayleigh backscattering of the fiber [13][14][15]. Thus, in this section we investigate the polarization-sensitive behavior of the FBG, by separating the S/P polarizations into the analysis.…”
Section: Polarization Analysismentioning
confidence: 95%
See 2 more Smart Citations
“…As previously outlined in [22], the MgO-NP fiber induces a beat length of polarization that has a higher frequency than a standard SMF, with polarization switching every few centimeters. This effect is common with the other methods proposed for enhancing the Rayleigh backscattering of the fiber [13][14][15]. Thus, in this section we investigate the polarization-sensitive behavior of the FBG, by separating the S/P polarizations into the analysis.…”
Section: Polarization Analysismentioning
confidence: 95%
“…Yan et al [13] reported a method based on rapid pulses with a fs laser (300 nJ at 250 kHz repetition rate), increasing the scattering level of a SMF by up to 45 dB. Parent et al [14] have obtained similar results, with a scattering increment of 37 dB, by means of exposure to intense ultraviolet light; this method has also been used to generate random gratings [15]. More recently, Beisenova et al [16] have obtained a 36.5 dB scattering increment by using a MgO-nanoparticle-doped (MgO-NP) fiber as sensing medium.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Shape sensors have been widely used in various fields ranging from civil 1 and aerospace 2 to medical applications. 3 Several methods for shape sensing have been reported over the years. Optical fibre sensors have been used to measure deflection as well as for reconstruction of the shape.…”
Section: Introductionmentioning
confidence: 99%
“…Due to the curvature data being discrete and obtained from the FBG sensors, the curvature is serialized continuously through the linear interpolation and the fitted algorithm; then the geometrical structure of the soft actuator can be reconstructed. By using the idea of differential calculus, a line with fixed length can be divided into several uniform sections, and the length of these sections expressed as L, namely O 1 O 2 = O 2 O 3 = L, and then become some arcs with the length of L when the microstructure is bending, and the center angle of the circular arc is determined by the length L and the curvature C. Assuming that the coordinate of O 2 is (0, 0), the coordinate of O 3 can be calculated as (sinθ 2 /C 2 , (1 − cosθ 2 /C 2 )), from the length L and curvature C, the θ 2 is equal to L*C 2 ; thus this algorithm can be applied for 3D shape reconstruction of the soft actuator [23][24][25][26][27][28][29].…”
Section: Principle Of Sensing and Measurement Of Embedded Fbgsmentioning
confidence: 99%